Simulated gravity field estimation for Deimos based on spacecraft tracking data - Su, Wenjie; Yan, Jianguo; Sun, Shangbiao; Yang, Yongzhang; Liu, Shanhong; Wang, Zhen; Barriot, Jean-Pierre (Frontiers in Astronomy and Space Sciences, 2024)
An accurate gravity field model of Deimos can provide constraints for its internal structure modeling, and offer evidence for explaining scientific issues such as the origin of Mars and its moons, and the evolution of the Solar System. The Japanese Martian Moon Exploration (MMX) mission will be launched in the coming years, with a plan to reach Martian orbit after 1 year. However, there is a lack of executed missions targeting Deimos and research on high-precision gravity field of Deimos at this stage. In this study, a 20th-degree gravity field model of Deimos was constructed by scaling the gravity field coefficients of Phobos and combining them with an existing low-degree gravity field model of Deimos. Using simulated ground tracking data generated by three stations of the Chinese Deep Space Network, we simulate precise tracking of a spacecraft in both flyby and orbiting scenarios around Deimos, and the gravity field coefficients of Deimos have been concurrently computed. Comparative experiments have been conducted to explore factors affecting the solution, indicating that the spacecraft’s orbital altitude, the noise level of observation data, and the ephemeris error of Deimos have a significant impact on the solution results. The results of this study can provide references for planning and implementation of missions targeting Martian moons.